Chaudhuriomyia, a new tanypod genus of Macropelopiini (Diptera: Chironomidae: Tanypodinae) from the Eastern Himalaya - Paul, Nilotpol; Mazumdar, Abhijit (Zootaxa, 2015)
A new genus, Chaudhuriomyia in the tribe Macropelopiini belonging to subfamily Tanypodinae is described and illustrated in all life stages. The genus can be distinguished from all the other known Macropelopiini by the presence of a blunt claw on fore leg and a smooth surface of tibial spur in adult male, seminal capsules without proper neck in adult female, round anal lobe in pupa, and slightly inwardly bent inner tooth of ligula in larva. Generic diagnoses for larva, pupa and adult are provided. Taxonomic position and distribution of the genus are discussed along with a new adult key of tribe Macropelopiini. The specimens were collected from a stream in Indo-Bhutan border area of Eastern Himalaya in Indian Subcontinent. A note on the ecology and biology of the new genus is included.